2004
DOI: 10.1002/eji.200324756
|View full text |Cite
|
Sign up to set email alerts
|

Expression of inhibitory KIR is confined to CD8+ effector T cells and limits their proliferative capacity

Abstract: A subset of effector/memory CD8 + T cells expresses natural killer cell receptors (NKR). Expression of inhibitory NKR at that stage of T cell differentiation is poorly understood. Interestingly, recent studies in mice indicated that transgenic expression of an inhibitory NKR induced the accumulation of memory T cells by inhibiting activation-induced cell death (AICD). To further understand the role of inhibitory NKR on T cells, we characterized the subset of human peripheral T cells expressing the inhibitory N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 47 publications
3
27
1
Order By: Relevance
“…In parallel with the previously described work on mice, several studies conducted in the early 2000s demonstrated the existence in humans of CD8(+) T cell-expressing markers and receptors of NK cells including CD56, KIR, NKG2A and NKG2C (CD159a and c), and CD94 (3136). Several studies precisely characterized the phenotype of the KIR(+) CD8(+) T cells and showed that they possess an EMRA memory phenotype [CD45RA(+) CCR7(−) CD57(+)] (33, 34).…”
Section: Evidence For Nk-like Cd8(+) T Cells In Humansmentioning
confidence: 53%
“…In parallel with the previously described work on mice, several studies conducted in the early 2000s demonstrated the existence in humans of CD8(+) T cell-expressing markers and receptors of NK cells including CD56, KIR, NKG2A and NKG2C (CD159a and c), and CD94 (3136). Several studies precisely characterized the phenotype of the KIR(+) CD8(+) T cells and showed that they possess an EMRA memory phenotype [CD45RA(+) CCR7(−) CD57(+)] (33, 34).…”
Section: Evidence For Nk-like Cd8(+) T Cells In Humansmentioning
confidence: 53%
“…Although KIR-expressing CD8 + T cells exist in human peripheral blood [38], the stimuli that regulate KIR induction in T cells are poorly defined [39], and may include demethylation events [40]. Interestingly, engagement of CD158b by MHC ligands on human CD8 + effector T cells hinders TCR signaling and limits T-cell proliferation [41]. Based on our findings, it is tempting to speculate that TG provided an in vitro signal orchestrating the expression of KIR on CIK cells.…”
Section: Discussionmentioning
confidence: 99%
“…APRIL and actin primers for RT-PCR have been previously described (22). Quantitative RT-PCR was done as previously described with a light cycler System (Roche Diagnostics) and the Quantitect SYBR Green PCR kit solution (QIAGEN) (55). For hAPRIL, 5′-ATGGGTCAGGTGGTGTCTCG-3′ and 5′-ATGGGT-CAGGTGGTGTCTCG-3′ were used as forward and reverse primers, respectively.…”
Section: Methodsmentioning
confidence: 99%